2006
DOI: 10.1007/s11427-005-0181-0
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling in porcine mammary gland during lactation and identification of breed-and developmental-stage-specific genes

Abstract: A total of 28941 ESTs were sequenced from five 5'-directed non-normalized cDNA libraries, which were assembled into 2212 contigs and 5642 singlets using CAP3. These sequences were annotated and clustered into 6857 unique genes, 2072 of which having no functional annotations were considered as novel genes. These genes were further classified into Gene Ontology categories. By comparing the expression profiles, we identified some breed- and developmental-stage-specific gene groups. These genes may be relative to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
3
6
0
1
Order By: Relevance
“…Several of the top lactation-associated genes are related to fatty acid metabolisms, in agreement with the results of research conducted on porcine mammary gland development [3]. One example is Cidea, which regulates lipolysis through the negative control of tumor necrosis factor-alpha (TNF-alpha) transcription in human adipocytes [37] and possibly perhaps via monitoring of lipid droplet size [38].…”
Section: Decisive Changes In Both Hk and Ms Gene Regulation During Thsupporting
confidence: 78%
See 1 more Smart Citation
“…Several of the top lactation-associated genes are related to fatty acid metabolisms, in agreement with the results of research conducted on porcine mammary gland development [3]. One example is Cidea, which regulates lipolysis through the negative control of tumor necrosis factor-alpha (TNF-alpha) transcription in human adipocytes [37] and possibly perhaps via monitoring of lipid droplet size [38].…”
Section: Decisive Changes In Both Hk and Ms Gene Regulation During Thsupporting
confidence: 78%
“…Linnaeus, recognizing their uniqueness in that female mammals nurse their young with milk produced by the mammary glands, classified the mammary-gland-bearing animals as belonging to the class Mammalia [2]. As one of the mammal-specific organs, the mammary gland has been widely studied at the molecular level [3], with many studies being micro-array-based [46]. For example, Clarkson et al [5] performed microarray studies and identified the difference in gene expression over 12 time points during mouse mammogenesis.…”
mentioning
confidence: 99%
“…The ESTs will be a valuable source for many researchers working with tumor tissue [8] . These ESTs, especially specific for canine mammary gland tissue, provide significant information for canine mammary cancer studies.…”
Section: Discussionmentioning
confidence: 99%
“…The mammary gland is an excellent system to study questions about organogenesis, cell differentiation and oncogenesis [8] . The most commonly diagnosed neoplasm in female dogs is mammary-gland tumor which is of an epithelial origin, and approximately 50% are malignant [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high level of protein synthesis in the lactation phase, expression of the proteins that participate in ribosomal structure increases at the preparation lactation stage. Also, the genes that have function in transcriptional and translational regulation are expressed highly before parturition [27]. Additionally, we have observed known putative genes related to immune system, growth, and lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%